PEMBELAJARAN DENGAN BAHAN AJAR BERBASIS MASALAH UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH PADA MATA KULIAH ANALISIS VEKTOR MAHASISWA SEMESTER IV PRODI PENDIDIKAN MATEMATIKA TAHUN PELAJARAN 2015/2016 - T. Tutut Widiastuti (Department of Mathematics Education, Universitas Kuningan, 2017)
Â AbstractÂ The purpose of thi research is to describethe ability of solving problems through the application of learning with a problem based teaching materials on the subject of vector analysis 4th semester students of mathematics education study program in the academic year 2015/2016. This study used a qualitative approach with classroom action research participants. The hallmark of the classroom action research done in the cycles. Each cycles consists of four phases: planning, implementation, observation, and reflection. Based on the results of this research is: (1) that students problem solving abilities views of mastery learning students has increased 23% , (2) From the average value of problem solving ability of students increased by 4,2 after improvements in cycle II, (3) Based on observation, the learning process has increased by 9,1% and student activities increased by 6,25%, (4) The all object of the interview stated that they were pleased with applied learning. From all the research results have shown that this research has met the success criteria set.Â